2015
DOI: 10.1245/s10434-015-4746-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Conserving Surgery in Bilateral Breast Cancer

Abstract: Background Bilateral breast cancer (BBC) may present as synchronous(SBC) or metachronous breast cancer(MBC). Optimal surgical management of BBC patients is not well defined. Here we report on histopathology, treatment, and outcomes in BBC patients. Methods Upon IRB approval, we identified BBC patients diagnosed and treated for invasive breast cancer between 1999–2007. Retrospective chart review for demographics, histopathology, treatment, and outcomes was performed. Factors associated with BCS choice were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Among the 15 included studies, five studies were from Europe, two from North America, five from Asia, one from Africa, and two from Australia . The sample size of included studies ranged from 110 to 34 557 and totally 75 214 participants were enrolled, including 72 302 UBC and 2912 BBC (1842 SBBC, 946 MBBC and 124 BBC with unknown interval).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 15 included studies, five studies were from Europe, two from North America, five from Asia, one from Africa, and two from Australia . The sample size of included studies ranged from 110 to 34 557 and totally 75 214 participants were enrolled, including 72 302 UBC and 2912 BBC (1842 SBBC, 946 MBBC and 124 BBC with unknown interval).…”
Section: Resultsmentioning
confidence: 99%
“…These studies were divided into three groups based on the interval time to differentiate SBBC from MBBC (3, 6 and 12 months). The study from O'Brien et al used both 3 and 6 months as interval cut‐off (SBBC ≤ 3 months while MBBC > 6 months, Table ), hence it was included in the meta‐analysis of both groups (Figure A,B). Three studies used 3 months as the interval, the summary HR of SBBC vs MBBC was 0.64 (95% CI = 0.44‐0.94) without heterogeneity (I 2 = 58%, P = 0.09) (Table , Figure A,D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective survey study, Shelby et al reported that young breast cancer survivors were less likely to undergo repeated mammograms (22). In a retrospective chart review, O'Brien et al found that although overall survival was similar in metachronous (MBC) and synchronous breast cancer, patients in the MBC group with discordant ER receptor status and an overall worse prognosis (23). In our study, we found that young patients were also more likely to develop a node-positive mCBC.…”
Section: Discussionmentioning
confidence: 99%